Trójsektorowość podejścia LEADER w założeniach i w praktyce wdrażania w okresie programowania 2007–2013 na przykładzie województwa śląskiego = Tri-sector partnership in LEADER approach in theory and practice in 2007-2013 programming period - an example of the Śląskie Voivodeship in Poland - Surmacz, Małgorzata; Magryś, Witold (PAN IGiPZ, 2016)
The main goal of the article was to evaluate the level of the individual sector involvement in tri-sector partnership in submitting LEADER programme projects (called “small projects”). The research was conducted in 15 Local Action Groups of the Śląskie Voivodeship, Poland; 3161 “small projects” submitted in 2009-2014 were analysed. The research has shown that:1) It seems that there is a considerable connection between the involvement level of each sector (social, private and public) in submitting LEADER projects and the development potential of each rural area in micro-regional context.2) The involvement level of social sector is quite high in every local action group, which can be regarded as a relative success of LEADER approach implementation in the Śląskie Voivodeship in Poland.3) The fact identified in other research that public sector is a major applicant in LEADER projects was confirmed. It could be considered as a real constraint in harmonic development of tri-sector partnerships in the future, but on the other hand it could be also a positive phenomenon, which enables LEADER implementation in these rural areas, where many obstacles limit access to LEADER funds by representation of the other sectors.These conclusions show that there is a great need of better promotion of LEADER approach especially among social and private sector. Moreover, it seems that LEADER requires a wide debate on its functions, real effects, and the role of public sector in LEADER programme implementation. It is particularly important in the current EU financial framework 2014-2020 in Poland as new regulations restrict the accessibility of LEADER funds for public sector.
24 cm
Keywords: LEADER; Silesia voivodship; tri-sector partnership; rank-and-file approach; small projects